The Impact of BPJS Ketenagakerjaan Participation on Corporate Risk Profile Changes: A Comparative Analysis Based on ISO 31000 - Aulia Rizki; Tanti Novianti; Linda Karlina Sari (Pelopor Publikasi Akademika, 2026)
The BPJS Employment Program is a labor social security system in Indonesia that is mandatory for companies and aims to provide protection against various employment risks. In addition to protecting workers, participation in this program also has the potential to affect a company’s risk profile. However, empirical studies that systematically analyze changes in corporate risk profiles before and after BPJS Ketenagakerjaan membership remain limited. Therefore, this study analyzes changes in corporate risk levels and examines their implications for risk management based on the ISO 31000:2018 framework. This study employs a descriptive-comparative quantitative approach using a before-and-after method. Primary data were obtained through questionnaires distributed to 39 companies participating in BPJS Ketenagakerjaan. Risk assessments cover four categories: legal, financial, operational, and reputational risks. Each is evaluated using likelihood and impact on a Likert scale of 1–5. Data analysis uses the geometric mean to derive representative values, followed by risk scoring and mapping onto a 5 × 5 risk matrix. The results indicate that BPJS Ketenagakerjaan membership alters corporate risk profiles. Legal and operational risks tend to decrease due to improved regulatory compliance and worker protection. Conversely, some financial and reputational risks increase, driven by contribution obligations and heightened stakeholder expectations. These findings suggest that BPJS Ketenagakerjaan acts as a risk transfer mechanism without fully eliminating risks, leaving residual risks that require ongoing control and monitoring. The study highlights that labor social security programs influence not only worker protection but also corporate risk dynamics from an organizational risk management perspective.